2017
DOI: 10.1093/jbcr/irx030
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Ascorbic Acid for Burn Shock Resuscitation May Not Improve Outcomes

Abstract: High dose ascorbic acid (HDAA) has been touted to ameliorate inflammation and reduce fluid requirements during burn shock resuscitation (BSR). Whether this leads to improved outcomes is not known. The authors' aim for this study was to compare ventilator days, ventilator-associated pneumonia, and mortality between patients who did and did not receive HDAA during BSR.The authors performed a retrospective case control study from 2012 to 2015. They identified 38 patients (HDAA) who received HDAA during BSR. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Our analysis among trials [16, 17, 19] suggested that AA intervention did not reduce the fluid requirement during the first 24 h of admission (SMD = − 0.52; 95% CI (− 1.63–0.58); p = 0.351; I 2 = 88.2%, Fig. 5).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Our analysis among trials [16, 17, 19] suggested that AA intervention did not reduce the fluid requirement during the first 24 h of admission (SMD = − 0.52; 95% CI (− 1.63–0.58); p = 0.351; I 2 = 88.2%, Fig. 5).…”
Section: Resultsmentioning
confidence: 89%
“…The characteristics of each trial are shown in Table 1. The studies recruited patients with severe sepsis or septic shock [15, 16, 20, 24], burn shock [1719], critical injury [21, 22], post-operation [14, 16, 36], trauma [36] and those in need of contrast-enhanced CT in the ICU [23]. The sample sizes ranged from 20 to 595.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations